Penggunaan Media Puzz Le Untuk Memotivasi Belajar Membaca Siswa Kelas 1 Di Sd Tanwirul Afkar - Febri Astuti, Ninis; Kartika Prameswari, Noviardani (Prodi Pendidikan Guru Sekolah Dasar, 2025)
This research aims to describe the use of puzzle media to motivate reading learning grade 1 students at Tanwirul Afkar Elementary School. This study uses a qualitative methodology, gathering data through observation, interviews, and documentation. Data collection techniques include observation, interviews and documentation with research subjects as many as 16 students. According to the study's findings, the procedure of using puzzle media was quite effective in learning, students who were previously unable to read now understood and were able to read. And based on the results of interviews, students were able to understand the material in the questions given by the teacher, students were very happy and enthusiastic when using puzzle learning media in learning, because this puzzle learning media is considered unique and pictorial so many students are enthusiastic about learning. Students can become more familiar with letters and learn to read, learning becomes fun and memorable, if they continue to be trained and given learning with appropriate models and media, they can provide the best results.